PERBANDINGAN LEGENDA ANGLINGDARMA DI MASYARAKAT BOJONEGORO DAN SÄRAT ANGLINGDARMA - , FITRI CANTIYAS STERIA HIDAYATI; , Dr. Wisma Nugraha Ch. R., M.Hum. dan Drs. Anung Tedjowirawan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Story of Anglingdarma is one of the famous legends among Javanese people, especially for the people in the village of Wotan Ngare, District of Kalitidu, Bojonegoro, East Java. Kalitidu society believes in the existence Anglingdarma legend contained in the region. The legend in Kalitidu (society) was reproduced by the government through a research and was published as Jejak Penelusuran Petilasan Anglingdarma Bojonegoro. This will compared both of the study result and literature written versions by a poet as SÄrat Anglingdarma collection of Sasana Pustaka Library of Keraton Surakarta have transliterated. There are the characters, plots, and places that are used in both versions. The comparison between those two version of Anglingdarma sotries has an aim to explain to the readers about the difference. The synopsis of Anglingdarma will be explaining although a little with the other literary such as SÄrat Purusangkara, SÄrat Pustakaraja, etc. It is intended to add a review of the literature Anglingdarma story than both of versions. The literary possible also have in common than differences among each other. As in the oral version tells the whole story of Anglingdarma that are not on SÄrat Anglingdarma version. However both versions have almost the same story line. It is same as when compared with other literary that have similarities and differences.